Green Accounting sebagai Pilar ESG: Peran Green Accounting dalam Mewujudkan CSR yang Akuntabel - Riky Sai Maruli (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study explores the role of green accounting as a foundation for accountability in implementing Corporate Social Responsibility (CSR) within the Environmental, Social, and Governance (ESG) framework. The research focuses on companies in Indonesia that actively integrate ESG principles into their business practices. The core problem addressed in this study is the lack of empirical understanding of how green accounting contributes to transparent and accountable CSR reporting, particularly in emerging economies where regulatory frameworks are still evolving. The objective is to investigate the extent to which green accounting practices support sustainable reporting and organizational decision-making. Employing a qualitative descriptive method, this research utilizes in-depth interviews with key informants, including financial managers, CSR officers, and environmental accountants from two companies implementing ESG-based strategies. The findings reveal that green accounting not only enhances the transparency of environmental performance but also facilitates internal collaboration, data-based decision-making, and risk mitigation. Challenges identified include the absence of standardized national guidelines, limited human resource competence, and the risk of greenwashing. However, the integration of digital technologies in reporting processes significantly improves the efficiency and reliability of sustainability disclosures. This research contributes new empirical insights into the practical application of green accounting in a developing country context and provides recommendations for policy enhancement, organizational capacity building, and ethical sustainability reporting systems. In conclusion, green accounting emerges as a strategic and operational tool that strengthens CSR accountability and supports the long-term sustainability goals of corporations.